PARADIGMA HAK KEBENDAAN KEPEMILIKAN SARUSUN YANG DIBANGUN PADA LAHAN HAK GUNA BANGUNAN - Roestamy, Martin (DE'RECHTSSTAAT, 2016)
Of the title "The Legal Paradigm of the properties on the strata title ownership built above the land with the Right to Cultivate Ownership" research objectives to be at said is knowing why the legal construction of the right material from the strata title built on land rights, attached to the Rights of material the building as common property rights and know how reconstruction material rights on the Strata titles built on building rights or rights of use that reflects justice and legal certainty. With the concept of methodologies theories and research approaches, as well as of the problems of this study concludes that there are a couple of things. First by sticking the land rights of the unit, then Strata titles have a dependency on the bottom right HGB as with all buildings owned and also can weaken the property rights of apartment units as the strongest and most, but became assessors of HGB. This situation raises a negative implication in the community and has created legal uncertainty and considered unfair, weakening the material rights of Strata titles caused dualism applicable law, the law of the land, building law and the law of objects. It affects the mutual intervention and debilitates the material rights as stipulated in the rules of the law of things, namely; droit de suite, droit de preverent, and droit de levering. In construction law, state that debilitates the legal certainty and justice, it can be reconstructed from the perspective of the development of the legal system of the building against the law of the land, or to the development of HGB as of right down with some simulations and restoration of existing government regulations, or reconstruct the principal laws agrarian related lease rights, land rights, and the rights of use by developing existing government regulations become law, so the law on the new ground by adding the rights of others. In a reconstruction of the law of the land, which is more competitive and create legal certainty and fairness.